FACTORS INHIBITING MOTHERS IN PROVIDING EXCLUSIVE BREASTFEEDING TO INFANTS AT PMB NURLELA LUBUK PAKAM SUBDISTRICT DELI SERDANG REGENCY IN 2024 - Marliani, Marliani; Anggraini , Mia; Surbakti , Imran Saputra; Astria , Nila; Lusiatun, Lusiatun (Yayasan Nuraini Ibrahim Mandiri, 2025)
Background: Exclusive breastfeeding for the first six months of life is recommended by WHO and UNICEF to ensure optimal infant growth and development. However, exclusive breastfeeding coverage in Indonesia, including Deli Serdang Regency, remains low. Several factors can hinder exclusive breastfeeding, including maternal knowledge, occupation, and the role of healthcare workers. Objective: To determine the factors inhibiting exclusive breastfeeding among mothers with infants at PMB Nurlela, Lubuk Pakam Subdistrict, Deli Serdang Regency, in 2024. Methods: This study used a cross-sectional design with a quantitative approach. The sample consisted of 30 mothers with infants aged 0–12 months who did not exclusively breastfeed. Data were collected through questionnaires and analyzed using univariate analysis to describe the frequency distribution of each variable.Results: The majority of respondents were aged 20–35 years (53.3%), had a senior high school education (46.7%), and worked as housewives (43.4%). Most respondents had a moderate level of knowledge about exclusive breastfeeding (43.3%), rated the role of healthcare workers as good (83.3%), and did not exclusively breastfeed (66.7%). Statistical tests showed that maternal knowledge (p = 0.006), occupation (p = 0.003), and the role of healthcare workers (p = 0.006) were associated with exclusive breastfeeding practices.Conclusion: Maternal knowledge, occupation, and the role of healthcare workers are significant factors inhibiting exclusive breastfeeding at PMB Nurlela. Efforts to improve exclusive breastfeeding rates should focus on continuous education, workplace support for breastfeeding mothers, and optimizing the role of healthcare workers.